Comparative Study on the Choice of Regulatory Models for the Formulation of Corruption Crimes in the Anti-Corruption Laws of Indonesia and Malaysia: Studi Komparatif Pemilihan Bentuk Pengaturan Tentang Model Penyusunan Tindak Pidana Korupsi dalam Undang-Undang Tindak Pidana Korupsi Indonesia dan Malaysia - Ridwan; Setiadi, Edi; Yulia, Rena; Heniarti, Dini Dewi; Batubara, Gialdah Tapiansari; Jaya, Belardo Prasetya Mega (LITIGASI, 2025)
Corruption in Indonesia has occurred at all levels of society as if corruption in Indonesia is never-ending to be discussed. Many law enforcers are involved in corruption, causing a community confidence crisis. Regardless, on the other hand, society is also apathetic and permissive towards criminal acts of corruption; society is also a contributor to corruption, especially in the implementation of the general and regional elections. It happens because of the perception that money politics is a natural thing in an imperfect democracy. This condition occurs because it is supported by the weak legal substance related to the crime of corruption. The weak legal substance is caused by legislative process errors, resulting in errors at the application and execution stages. So, it is necessary to examine the model of drafting laws related to the crime of corruption using normative juridical methods, namely analysing various laws related to the crime of corruption with a comparative approach by comparing the model of Indonesia's and Malaysia's anti-corruption laws drafting. The results showed that the drafting of corruption crimes in Indonesia is spread in several laws that can potentially cause disparities in justice. On the other hand, the drafting model of corruption crimes in Indonesia is carried out by separating the Criminal Code from the anti-corruption law, while in Malaysia, the drafting of the anti-corruption law is mutually reinforcing with the Penal Code.